Influence of dietary patterns and physical activity on bone mineral content and density, osteoporosis among children with stimulant use - Li, Qianqian; Zhou, Jiaxiu (Frontiers in Pediatrics, 2022)
Aim: To examine the relationship between dietary patterns (DPs) and physical activity (PA) on bone mineral content (BMC) and bone mineral density (BMD), osteoporosis in children with stimulant use. Methods: A cross-sectional study collected information of participants from National Health and Nutrition Examination Survey (NHANES) via multistage stratified sampling. Baseline variables included the following: age, gender, the Dietary Approaches to Stop Hypertension (DASH) score, the Mediterranean diet (MD) score, and the Alternative Healthy Eating Index-2010 (AHEI-2010), etc. Univariate and multivariate linear-regression analyses were carried out to explore the statistical correlation between the DPs and PA on BMC and BMD in children with stimulant use or non-stimulant use. Additionally, we also investigated the association between DPs and PA on osteoporosis via logistic regression analyses. Results: A total of 6,294 participants were eligibly enrolled in this study eventually. After adjusted age, gender, body mass index (BMI), race, family income, serum 25-hydroxyvitamin D, serum cotinine, the multivariate linear-regression analysis showed MD was positively associated with total femur BMD, total femur BMC, femoral neck BMD, femoral neck BMC among stimulant use group; high PA was associated with total femur BMD, total femur BMC, femoral neck BMD, femoral neck BMC, lumbar spine BMD, lumbar spine BMC and osteoporosis in stimulant use group. Conclusion: Improved the adherence to MD, DASH, AHEI-2010 or increased physical activity may increase BMD, BMC and reduce the risk of osteoporosis; children with stimulant use should improve the adherence to the MD and do more PA compared with children without stimulant use.